Deviating from the social consensus: Relations among the Dark Triad, moral normativity, and general social normativity. (1st June 2020) - Kay, Cameron S.; Saucier, Gerard
Highlights: We examined relations among the Dark Triad traits and two types of normativity. Psychopathic individuals appeared to be less attuned to the morality of traits. They also appeared to be less aware of the social desirability of traits. Machiavellianism and narcissism were not consistently associated with any such deficit. Abstract: There are two plausible hypotheses for why those high in the Dark Triad traits (Machiavellianism, narcissism, and psychopathy) behave immorally: (1) They do not understand morality and are, consequently, unable to act morally or (2) they understand morality but simply disregard it when deciding how to act. In two studies, we tested these hypotheses by examining relations among the Dark Triad traits and a novel measure of moral normativity—a person's understanding of what is and is not a moral way to be—and general social normativity—a person's understanding of what is and is not a socially desirable way to be. Consistent with the first hypothesis, psychopathic individuals were less attuned to the morality of traits. Critically, their inability to understand what was socially desirable was attributable, at least in part, to an inability to understand what was moral. Those scoring high in Machiavellianism and narcissism showed no such deficits.